Birth mode, breastfeeding and childhood infectious morbidity in the Yucatec Maya. Issue 2 (31st January 2019) - Veile, Amanda; Faria, Amy A.; Rivera, Sydney; Tuller, Sydney M.; Kramer, Karen L.
Abstract: Objectives: Cesarean delivery is linked to breastfeeding complications and child morbidity. These outcomes may disproportionately affect Latin American indigenous populations that are experiencing rising cesarean delivery rates, but often inhabit environments that exacerbate postnatal morbidity risks. We therefore assess relationships between birth mode, infant feeding practices, and childhood infectious morbidity in a modernizing Yucatec Maya community, where prolonged breastfeeding is the norm. We predicted that under these conditions, cesarean delivery would increase risk of childhood infectious morbidity, but prolonged breastfeeding postcesarean would mitigate morbidity risk. Methods: Using a longitudinal child health dataset (n = 88 children aged 0‐60 months, 24% cesarean‐delivered, 2290 observations total), we compare gastrointestinal infectious (GI) and respiratory infectious (RI) morbidity rates by birth mode. We model associations between cesarean delivery and breastfeeding duration, formula feeding and child nutritional status, then model GI and RI as a function of birth mode, child age, and feeding practices. Results: Cesarean delivery was associated with longer breastfeeding durations and higher child weight‐for‐age, but not with formula feeding, GI, or RI. Adolescent motherhood and RI were risk factors for GI; formula feeding and GI were risk factors for RI. Regional housing materials protected against GI; breastfeeding protected against RI and mitigated the effect of formula feeding. Conclusions: We find no direct link between birth mode and child infectious morbidity. Yucatec Maya mothers practice prolonged breastfeeding, especially postcesarean, and in conjunction with formula feeding. This practice protects against childhood RI, but not GI, perhaps because GI is more susceptible to maternal and household factors.